1980
DOI: 10.1111/j.1600-0528.1980.tb01309.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral conditions in Australian children of Aboriginal and Caucasian descent

Abstract: Oral health parameters were examined for 211 schoolchildren (128 Aborigines and 83 Caucasians) representative of the 6--8 and 10--11 year age groups in the Brewarrina and Walgett areas of western New South Wales (fluoride in water less than or equal to 0.02-0.26 parts/10(6)). Despite similar dietary carbohydrate challenge and tooth eruption patterns, Aboriginal children, most of whom were members of a transitional community within a low socioeconomic stratum, had higher prevalence of caries (DIMFT) and severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 4 publications
(2 reference statements)
0
35
0
1
Order By: Relevance
“…One study collected data from two jurisdictions, 14 one study collected data from all jurisdictions except the Australian Capital Territory and Tasmania 20 and one study 17 did not report the location from where the data were collected. Across these jurisdictions, four studies 16,18,26,36 (40%) reported on Indigenous adults living only in rural locations, five studies 14,20,24,27,28 reported on Indigenous adults living in both urban and rural locations (with most reporting data for the total population in the sample rather than reporting the data by urban or rural location) and one study reported only on an urban sample. 17 Figure 2 summarises the number of studies publishing data for each jurisdiction, with total Indigenous population numbers.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study collected data from two jurisdictions, 14 one study collected data from all jurisdictions except the Australian Capital Territory and Tasmania 20 and one study 17 did not report the location from where the data were collected. Across these jurisdictions, four studies 16,18,26,36 (40%) reported on Indigenous adults living only in rural locations, five studies 14,20,24,27,28 reported on Indigenous adults living in both urban and rural locations (with most reporting data for the total population in the sample rather than reporting the data by urban or rural location) and one study reported only on an urban sample. 17 Figure 2 summarises the number of studies publishing data for each jurisdiction, with total Indigenous population numbers.…”
Section: Search Resultsmentioning
confidence: 99%
“…17 Figure 2 summarises the number of studies publishing data for each jurisdiction, with total Indigenous population numbers. Only two studies 26,36 (20%) reported the fluoride status of the study's location. Data were presented using a variety of age groupings, which makes comparisons between studies difficult.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations